Analisis Data Arah Dan Kecepatan Angin Landas Pacu (Runway) Menggunakan Aplikasi Windrose Plot (Wrplot) - Fadholi, Akhmad (JIK: Jurnal Ilmu Komputer, 2013)
Wind speed and direction are required in planning and development of runway around airport. As one of the fundamental considerations, wind data must be processed and analyzed to be usefull information especially in wind rose diagram form. But, to do a lot o wind data need a software to do a fast calculation and presenting anlysis results well. Lakes Environmental is a corporation produce software such as WRPLOT (Wind Rose Plot) to do fast calculation, presenting wind rose diagram and distribution frequency graph. Furthermore, it can export the wind rose diagram which is result of WRPLOT calculation in google map. So, user can see the information of wind speed and direction of runway like in real condition.Keywords: wind analysis, wind rose, WRPLOT